Gradually including potential users: A tool to counter design exclusions - Zitkus, Emilene; Langdon, Patrick; Clarkson, P. John (Elsevier B.V., 2018)
The paper describes an iterative development process used to understand the suitability of different inclusive design evaluation tools applied into design practices. At the end of this process, a tool named Inclusive Design Advisor was developed, combining data related to design features of small appliances with ergonomic task demands, anthropometric data and exclusion data. When auditing a new design the tool examines the exclusion that each design feature can cause, followed by objective recommendations directly related to its features. Interactively, it allows designers or clients to balance design changes with the exclusion caused. It presents the type of information that enables designers and clients to discuss user needs and make more inclusive design decisions. (C) 2017 Published by Elsevier Ltd.
Keywords: Ergonomic task demands; Design practice; Inclusive design tool; Design for all; Universal design